User acceptance of battery swapping in battery electric vehicles among private users in Germany - Jan Kegel; Jan Wiesenthal; Malte Welling; Aniket Kapse; Bernd Hirschl; Dirk Uwe Sauer (npj Sustainable Mobility and Transport, 2025)
Abstract The market ramp-up of battery electric vehicles (BEVs) continues to falter in Germany. One reason is missing user acceptance for BEVs, mainly due to insufficient range, inadequate charging infrastructure, and excessive costs. Many of these obstacles could be addressed through battery swapping stations. This study validates existing barriers to e-mobility, investigates whether battery swapping could alleviate existing barriers, and identifies potential concerns associated with battery swapping. This study is based on an online questionnaire completed by 1902 individuals representative of the German population. Results indicate that individuals interested in BEVs particularly recognize battery swapping as a problem solver. BEV owners also recognize the potential of swapping but have fewer concerns regarding e-mobility in the first place. A discrete choice experiment embedded in the survey revealed a willingness to pay an additional €56 per month for a BEV with swapping technology compared to a BEV with an integrated battery.